HTML5 quick markup reference - Jackson, Wallace (Expert's voice in Web development., 2016)
This book is a condensed reference for HTML5 markup. It presents the essential HTML5 elements and attributes in a well-organized format that can be used as a handy reference. HTML5 Quick Markup Reference is an HTML5 reference title covering tags and parameters central to HTML5 markup using the NetBeans 8.1 IDE. The book covers the tags used in HTML5, logically organized by topical chapters. It gets more advanced as chapters progress, covering the new media tags and file formats that are best for use with HTML5, as well as key factors regarding the data footprint optimization work process, in-lining .CSS and .JS files, and why data footprint optimization is important. What You Will Learn: The tags supported in HTML5 What comprises an HTML5 content production workflow Concepts and principles behind HTML5 content production How to install and utilize Inkscape for Windows, Mac OS X and Linux Concepts behind spline curves, strokes, fills, patterns, and rendering Digital illustration data formats and data footprint optimization Who This Book Is For: Website developers, Flash developers, user interface designers, HTML5 game designers, teachers, and educators.